Variasi Bahasa dan Interaksi Virtual Generasi Z pada Platform Roblox - Putri, Syalsa Ariesta Widya; Qanskamila, Alvina; Hasrianti, Hasrianti; anhar, Anhar (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study examines the language variation and virtual interaction patterns of Indonesian Generation Z on the Roblox platform. Employing a digital ethnography approach combined with multimodal discourse analysis, data were collected through participant observation, semi-structured interviews, and chat log analysis. The findings reveal five dominant communication patterns: (1) the prevalence of code-mixing (blending Indonesian and English), (2) a complex system of nonverbal communication through emotes and gestures, (3) the use of slang and abbreviations as identity markers, (4) sociolinguistic awareness in varying language registers based on social relations, and (5) the significant influence of globalization and digital content on language practices. These findings indicate that Generation Z develops multimodal communication competencies and forms unique hybrid linguistic identities by integrating local and global elements within the virtual space. This research contributes to the understanding of language evolution in the digital era and has implications for the development of digital literacy.